PENERAPAN TEKNOLOGI BIO-INPUT PERTANIAN SEBAGAI RENCANA AKSI PERTANIAN BERKELANJUTAN - Nurdin Nurdin; Wawan Pembengo; Fitriah S Jamin (Universitas Mataram, 2026)
Agriculture in Indonesia is generally characterized by monoculture planting systems, continuous use of fertilizers and pesticides, increased doses and frequency of application resulting in decreased fertility, structure and biotic balance of the soil, surface water and ground water pollution, are characteristics of agricultural models that are dangerous for the ecosystem and human health. Bio Input is an environmentally friendly agricultural input using existing resources to support agricultural production, economic improvement and conservation of natural resources, as well as the independence and welfare of farmers in a sustainable manner, but there are still many farmers who have not implemented it. The purpose of this activity is to apply agricultural bio-input technology through increasing knowledge and skills to groups of farmers and housewives as a sustainable agricultural action plan in Longalo Village. The methods used are socialization, training and direct practice of product making, while data analysis uses pre-test and post-test techniques. The results obtained show that bio input technology has been implemented by farmer groups and housewives in Longalo Village, as seen from the increase in knowledge and skills in: making eco-enzymes, which initially only 60.50 people knew, to 81.25 people who knew and could make them, making compost, which initially only 67 people knew, to 88.25 people who knew and could make them, and making biopesticides, which initially only 63 people knew, to 85.50 people who knew and could make them.